2015
DOI: 10.1002/jssc.201401344
|View full text |Cite
|
Sign up to set email alerts
|

Separation and concentration of sulfonylurea herbicides in milk by ionic‐liquid‐based foam flotation solid‐phase extraction

Abstract: The ultrasound-assisted ionic liquid foam flotation solid-phase extraction of sulfonylurea herbicides in milk was developed and validated. The proteins and lipids were isolated from the sample matrix by adding salt and adjusting the pH value. The target analytes eluted from the solid-phase extraction cartridge were determined by high-performance liquid chromatography. Some experimental parameters, including the pH value of sample solution, amount of NaCl, ionic liquid type, extraction time, flow rate of carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The performances of this method and previously published methods [28][29][30][31][32] for determining SUHs are shown in Supporting Information Table S4. The method gave satisfactory recoveries and similar or lower LODs and RSDs to the other methods.…”
Section: Comparison With Other Extraction Methodsmentioning
confidence: 99%
“…The performances of this method and previously published methods [28][29][30][31][32] for determining SUHs are shown in Supporting Information Table S4. The method gave satisfactory recoveries and similar or lower LODs and RSDs to the other methods.…”
Section: Comparison With Other Extraction Methodsmentioning
confidence: 99%
“…In addition to heavy metal ions, ion otation is also commonly used for removing organic and biological pollutants such as oil, triazine herbicides, peruorooctane sulfonate (PFOS) and peruorooctanoate, Rhodamine 6G and sulfonylurea herbicides from wastewater or aqueous solution. [41][42][43][44][45][46][47] Lignin removal research was conducted by Wang et al through ion otation using cetyl dimethyl benzyl ammonium as the surfactant. They found that a fraction of more than 0.95 could be removed by continuous ion otation under the optimum operational conditions.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…The main characteristics of ILs are low vapor pressure, good thermal stability, non‐volatile, low melting point, wide boiling range, strong electrostatic field, good conductivity, and thermal conductivity . It is a superior‐quality substitute of the traditional organic solvent in chemistry . These characteristics make ILs have properties of both liquid and solid.…”
Section: Introductionmentioning
confidence: 99%